Investigating the Demographic and Behavioural Predictors of Mental Health and Burnout in Medical Students: A Cross-Sectional Study - Morgan, Tamara (Université d'Ottawa / University of Ottawa, 2019)
Background: Medical students are at risk for poor mental health and burnout compared to the general population (Dyrbye et al., 2014). A preponderance of research has examined predictors of mental illness in medical students (Brazeau et al., 2014; Hope & Henderson, 2014). However, few studies have investigated predictors of mental health, and no studies to our knowledge have compared predictors of mental health and burnout in medical students. Further, several studies have assessed physical activity and burnout in medical students but these have neither examined specific intensities of physical activity nor have considered the role of sedentary behaviour in predicting medical student burnout (Dyrbye, Satele, & Shanafelt, 2017b; Wolf & Rosenstock, 2017). Thus, there is a dearth of knowledge on how demographics relate to mental health and burnout, and how mild, moderate, and vigorous physical activity, and sedentary behaviour relate to burnout in medical students. Purpose: To investigate and compare demographic predictors (gender, ethnicity, age, level of education, year of study, and proposed specialty) of mental health and burnout, to examine behavioural predictors (mild, moderate, vigorous, and total physical activity, and sedentary behaviour) of burnout, and to investigate moderate-to-vigorous physical activity as a moderator of the relationship between sitting and burnout in first to fourth year medical students. Methods: The sample consisted of 129 first to fourth year medical students at two large Canadian universities. Participants were recruited through electronic newsletters, medical student Facebook groups, and an in-class announcement. This study used a cross-sectional design. Data were collected through online surveys of validated self-report questionnaires measuring demographics, mild, moderate, vigorous, and total physical activity, sitting, mental health, and burnout. Results: Third year of study was a significant negative predictor of mental health while female gender, ‘other’ ethnicity and third year of study were significant positive predictors of burnout. Moreover, female gender, ‘other’ ethnicity, and fourth year of study predicted mental health differently from burnout. Second and third year of study predicted mental health and burnout similarly. Mild physical activity and sitting were significant negative predictors of burnout. Moderate-to-vigorous physical activity was not a significant moderator of the relationship between sitting and burnout. Conclusions: Findings of this study support Keyes’ Dual Continua Model (2014) and Maslach’s theorization of burnout (Maslach, Jackson, & Leiter, 1996) and can inform targeted programs to prevent poor mental health and burnout in medical students. Future research is recommended on these key topics.
Keywords: mental health; burnout; medical student; physical activity; sedentary behaviour; year of study; gender; ethnicity